PENGARUH KOMBINASI DOSIS PUPUK NPK (15:15:15) DAN KCL TERHADAP PERTUMBUHAN DAN HASIL TANAMAN EDAMAME (Glycine max (L.) Merril) VARIETAS RYOKO-75: Bahasa Indonesia - Yudi Yusdian; Dian Murti Minangsih; Dian Herawati (Program Studi Agroteknologi Faperta UNIBBA, 2023)
This study aims to determine and study the effect of the best combination dosage of NPK (15:15:15) and KCl fertilizer on the growth and yield of edamame (Glycine max (L.) Merrill) Ryoko-75 variety. The experiment was carried out in Sukamaju Village, Cimaung District, Bandung Regency, West Java Province, with an altitude of 860 meters above sea level. With a rainfall of 2417.40 mm/year, according to Oldeman (1975), it belongs to the C3 type of rainfall, with a pH of 5.74. The research method used was an experimental method using a Randomized Block Design (RBD) which consisted of 6 treatments and was repeated 4 times so that there were 24 experimental plots. The levels of treatment are: A (100 kg/ha NPK + 250 kg/ha KCl), B (150 kg/ha NPK + 200 kg/ha KCl), C (200 kg/ha NPK + 150 kg/ha KCl), D (250 kg/ha NPK + 100 kg/ha KCl), E (300 kg/ha NPK + 50 kg/ha KCl) and F (350 kg/ha NPK + 0 kg/ha KCl). The results showed that the dosage of 350 kg/ha NPK + 0 kg/ha KCl gave a better effect on plant height, number of pods per plant, pod weight per plant and pod weight per plot of edamame (Glycine max (L.) Merrill) plants. Ryoko-75 variety.